Gendered Humor and Stylistic Play in Modern Feminist Theatre: A Pragmatic-Stylistic Approach - Dahlan (Indonesian TESOL Journal, 2025)
This study explores the intersection of gendered humor, stylistic innovation, and pragmatic subversion in modern feminist theatre, focusing on works by Caryl Churchill, Sarah Ruhl, and Ntozake Shange. These playwrights employ humor not merely as entertainment but as a discursive weapon to challenge patriarchal norms, expose socio-political absurdities, and redefine gendered subjectivities. Drawing on frameworks from, stylistics, and pragmatics—particularly politeness theory, speech act theory, and incongruity theory of humor—this research investigates how stylistic choices (e.g., fragmentation, surrealism, poetic language) intertwine with humor strategy articulate feminist resistance. By analyzing selected scenes from Top Girls (Churchill), The Clean House (Ruhl), and for colored girls who have considered suicide / when the rainbow is enuf (Shange), the research reveals how humor in feminist drama functions both as a coping mechanism and as a mode of critique. This study contributes to feminist stylistics by offering a nuanced account of how gendered language and stylistic form shape subversive humor. Ultimately, it foregrounds how female playwrights turn theatrical space into a site of both laughter and liberation.